The accommodation of Muslim body practices in German public swimming pools - Ines Michalowski; Max Behrendt (Ethnic and Racial Studies, 2020)
The renegotiation of secularity for Muslims has reached sports facilities such as swimming pools, where the human body is central and an element of cross-cultural contestation. The present study identifies factors that could explain intra-organizational variations in religious accommodation. Data from a survey of geo-located swimming pools in Germany (n0.167em=0.167em339) shows that conflict among users becomes more likely if the variation in body practices, the share of right-wing populist votes and the population of immigrant background increases. On the organizational level, we find that 75 per cent of the pools in our sample allow the burqini while only 10 per cent provide separate swimming hours for women. Higher shares of right-wing populist (and to a lesser extent of conservative) votes in the organization's environment correlate with a higher likelihood of burqini bans. Our findings suggest that the relationship between organizational change and citizens' attitudes is loose at best.
Keywords: 330; organization; religious accommodation; swimming pools; immigrant integration; Muslims